2016
DOI: 10.1007/s00592-016-0857-x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length is independently associated with subclinical atherosclerosis in subjects with type 2 diabetes: a cross-sectional study

Abstract: LTL is an independent predictor of subclinical atherosclerosis pointing to a role of LTL as an early marker of vascular burden and cardiovascular disease also in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In the Cox regression analysis using z score of rLTL and other risk factors for predicting CVD, the effect size of rLTL was similar to that of HbA 1c per SD change in risk factor. Other reports have demonstrated an association of rLTL with CVD risk factorsd including elevated LDL-C, raised blood pressure, poor glucose control, and carotid intima-media thicknessdin patients with diabetes (27,28). Cross-sectional studies of patients with type 2 diabetes showed that patients with previous MI or atherosclerotic plaques had shorter rLTL than did those without either (8,9,12).…”
Section: Discussionmentioning
confidence: 89%
“…In the Cox regression analysis using z score of rLTL and other risk factors for predicting CVD, the effect size of rLTL was similar to that of HbA 1c per SD change in risk factor. Other reports have demonstrated an association of rLTL with CVD risk factorsd including elevated LDL-C, raised blood pressure, poor glucose control, and carotid intima-media thicknessdin patients with diabetes (27,28). Cross-sectional studies of patients with type 2 diabetes showed that patients with previous MI or atherosclerotic plaques had shorter rLTL than did those without either (8,9,12).…”
Section: Discussionmentioning
confidence: 89%
“…Studies have proved that telomere length acts as an independent predictor of atherosclerosis, which is an early marker of vascular burden. [ 39 ] Other studies have suggested that there is a close relationship between carotid atherosclerosis and the occurrence of progressive ischemic stroke. [ 40 ] Besides, telomere length plays an important role in different stages of atherosclerosis, which is likely to cause stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, vascular telomere length is lower in T2D patients ( 162 ). This is also important as a recent cross-sectional study demonstrated that telomere length is independently associated with subclinical atherosclerosis in subjects with T2D ( 152 ). However, accelerated telomere attrition was recently reported in circulating leukocytes, but not arteries, in T2D compared to control rats ( 156 ).…”
Section: Accelerated Vascular Aging In Diabetesmentioning
confidence: 98%